PREVALENSI ANAK KESULITAN BERHITUNG DI SD: ASESMEN MATEMATIKA BERBASIS KURIKULUM - ARMY BINTORO, FATONI (Jurnal Pendidikan Khusus, 2016)
ABSTRACT  Prevalence is the number of a problem measured by using identification instrument and assessment to determine the sum and its percentage. The main problem of this research is children difficulty in counting. Difficult counting is the disability in doing arithmetic skill expected for intellectual and student education level given through individual test. Mathematic assessment test based curriculum is used to identify children who get problem in difficult counting at SDN Jabon 1 Jombang. Assessment is a process to collect information about a child used as consideration and judgment. The objective of this research is to identify children prevalence in counting problem at SDN Jabon 1 Jombang. Descriptive quantitative is used in this methodology research. Kind of this research uses survey research as design research. The technique of collecting data uses test, observation (checklist) and documentation. For research data analysis, the researcher uses simple formulation statistic percentage.  The result of this research indicates that students who get counting problem at SDN Jabon 1 Jombang from first class up to fourth class is 16 students (24%) 10 male students (15%) 6 female students (9%).   Keywords: Prevalence, assessment test.